Adolescent emotion scale for online lessons: A study from Turkey - Yilmaz, M. Betul; Orhan, Feza; Zeren, S. Gonca (SPRINGER, 2022)
People's day-to-day routines have changed drastically since the outbreak of the COVID-19 pandemic. One of the changes to take place has been the transition to online learning due to the changing conditions in learning environments. One of the factors that guide students through learning environments is their emotions. The few existing scales that measure the emotions of adolescents in learning environments have been developed with consideration of face-to-face learning environments and their items do not adequately express the state of online environments. For this reason, this study aimed to develop a scale which reveals the emotions of adolescents that may affect their academic success with regard to this transition of learning environments as they attend online lessons. A total of 3,655 middle and high school students living in Istanbul, Turkey, participated in the study. The scoring system was designed with regard to the frequency with which each student reading an item experiences the relevant emotion for the item in the online learning environment. Exploratory and confirmatory factor analyses conducted show the scale to possess a four-dimensional structure. These dimensions are enjoyment-pride, boredom-hopelessness, loneliness and anxiety. For all dimensions of the scale, Cronbach alpha values range between .93 and .83. 'Positive and Negative Affects Schedule-Children' was used to confirm the scale's criterion-related validity, and correlations between dimensions were examined. After validity and reliability studies, the Adolescent Emotion Scale for Online Lessons was found to be sufficient. The scale can be used by experts and teachers who wish to determine adolescents' emotions during a period of online learning.
Keywords: Adolescents; Academic emotion scale; Online learning environment; Online learning; Scale development; LIFE SATISFACTION SCALE; ACADEMIC EMOTIONS; ACHIEVEMENT EMOTIONS; EXPERIENCE; VALIDITY; TURKISH; Education & Educational Research